ANALYSIS OF MATERNAL AGE AND GESTATIONAL HYPERTENSION FACTORS ON THE RISK OF BBLR OCCURRENCE AT MEDICA CLINIC EAST MEDAN DISTRICT IN 2026 - Herlina; Noer Desmie (Journal of Public Health Science, 2026)
Maternalhealthhasabigroleindeterminingchildren'shealth.AccordingtotheHealthProfile, the InfantMortalityRate(AKB)inIndonesiahasdecreased,but it stillneedstoaccelerateeffortssothat the targetof16/1,000livebirthscanbe achieved.The biggest contributors of deathin2022wereLowBirthWeight(BBLR)(28.2%)andAsphyxia(25.3%).Thisresearchmethodusesquantitativeresearchwithacasecontroldesign..ThepurposeofthisstudyistodeterminetheRelationship between AgeandHypertensioninPregnantWomenwiththeIncidenceofBBLRattheKasihClinic,EastMedanDistrict,NorthSumatraProvincein2026.SamplingtechniquewithTotalSamplingwith100populationandsamples.Theresults of theChi-Squeretestshowedthattheage of pregnantwomenwithp-value=0.000(<0.05)andhypertensioninpregnantwomenwithp-value=0.010(<0.05).Theconclusion of thestudystatedthatthereisarelationship between ageandhypertensioninpregnantwomenandtheincidenceofBBLRat the KasihClinic,EastMedanDistrict,NorthSumatraProvincein2026.